Use of ketamine for treatment resistant depression: updated review of literature and practical applications to a community ketamine program in Edmonton, Alberta, Canada - Chrenek, Carson; Duong, Bryan; Khullar, Atul; McRee, Chris; Thomas, Rejish; Swainson, Jennifer (Frontiers in Psychiatry, 2024)
Background: Though intravenous (IV) ketamine and intranasal (IN) esketamine are noted to be efficacious for treatment-resistant depression (TRD), access to each of these treatments within healthcare systems is limited due to cost, availability, and/or monitoring requirements. IV ketamine has been offered at two public hospital sites in Edmonton, Canada since 2015. Since then, demand for maintenance ketamine treatments has grown. This has required creative solutions for safe, accessible, evidence-based patient care. Objectives: Aims of this paper are twofold. First, we will provide a synthesis of current knowledge with regards to the clinical use of ketamine for TRD. Consideration will be given regarding; off-label racemic ketamine uses versus FDA-approved intranasal esketamine, populations treated, inclusion/exclusion criteria, dosing, assessing clinical response, concomitant medications, and tolerability/safety. Second, this paper will describe our experience as a community case study in applying evidence-based treatment. We will describe application of the literature review to our clinical programming, and in particular focus on cost-effective maintenance treatments, long-term safety concerns, routes of ketamine administration other than via intravenous, and cautious prescribing of ketamine outside of clinically monitored settings. Methodology: We conducted a literature review of the on the use of ketamine for TRD up to June 30, 2023. Key findings are reviewed, and we describe their application to our ketamine program. Conclusions: Evidence for the use of ketamine in resistant depression has grown in recent years, with evolving data to support and direct its clinical use. There is an increasing body of evidence to guide judicious use of ketamine in various clinical circumstances, for a population of patients with a high burden of suffering and morbidity. While large-scale, randomized controlled trials, comparative studies, and longer-term treatment outcomes is lacking, this community case study illustrates that currently available evidence can be applied to real-world clinical settings with complex patients. As cost is often a significant barrier to accessing initial and/or maintenance IV or esketamine treatments, public ketamine programs may incorporate SL or IN ketamine to support a sustainable and accessible treatment model. Three of such models are described.